2020
DOI: 10.1016/j.sjbs.2020.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-silver nanoparticles and their impact on some environmental beneficial fungi

Abstract: Colloidal suspensions of silver nanoparticles (AgNPs) with surface modified by capping with citrate ions were synthesized by chemical reduction method. Transmission and Scanning Electron Microscopy as well as darkfield Optical Microscopy provided information on the nanoparticle morphology, with fine symmetrical grains and log-normal fitted size distribution. Small Angle X-ray Scattering method allowed theoretical confirmation of colloidal silver nanoparticle fine granularity, based on measurements in the nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…The two-step process promotes the efficient synthesis of Ag NPs since the reduction of silver ions is totally completed during the first step. As a result, the pH slightly increased from 5 to 6 while the SPR band maximum blue-shifted from 425 nm to 418 nm, suggesting the formation of smaller Ag NPs; this corroborates studies that reported the influence of increasing pH on the narrowing and position of the Ag NP SPR band [ 129 , 130 ].…”
Section: Synthesis Of Gold and Silver Nanoparticles Under Uv Light Irradiationsupporting
confidence: 89%
See 1 more Smart Citation
“…The two-step process promotes the efficient synthesis of Ag NPs since the reduction of silver ions is totally completed during the first step. As a result, the pH slightly increased from 5 to 6 while the SPR band maximum blue-shifted from 425 nm to 418 nm, suggesting the formation of smaller Ag NPs; this corroborates studies that reported the influence of increasing pH on the narrowing and position of the Ag NP SPR band [ 129 , 130 ].…”
Section: Synthesis Of Gold and Silver Nanoparticles Under Uv Light Irradiationsupporting
confidence: 89%
“…Some studies suggest that the Ag NP size tends to decrease in alkaline media due to the rapid nucleation, while acidic media results in larger Ag NPs since the reaction rate is slower [ 127 , 128 ]. Furthermore, the pH affects the absorption of light and the position of the localized SPR (LSPR) band [ 126 , 129 ]. Babusca et al synthesized Ag NPs via a two-step process: the aqueous mixture of AgNO 3 and trisodium citrate was heated then irradiated using a UV-C lamp (30 W) for 45 min [ 126 ].…”
Section: Synthesis Of Gold and Silver Nanoparticles Under Uv Light Irradiationmentioning
confidence: 99%
“…Just before the boiling point, 5 ml of 1% trisodium citrate was added drop by drop to this solution. Vigorous mixing was carried out during the process to increase the interaction of the reagents, the reaction mixture was maintained at over 60 °C, until its color changed to grey 10 .…”
Section: Preparation Of Fruit Extractmentioning
confidence: 99%
“…Soil cellulolytic fungal community was found to be easily influenced by exogenous additives. 25,26 For example, Pampulha and Oliveira 27 observed that combined application of bromoxynil and prosulfuron significantly decreased the abundance of the cellulolytic fungal community. Similarly, the addition of the medicinal herb Isatis indigotica strongly inhibited the growth of cellulolytic fungal groups such as Penicillium and Fusarium.…”
Section: Introductionmentioning
confidence: 99%